The official list of procedures (Journal of Parents and Teachers, 1996)
Textbooks and newspapers are compared in the educational field, highlighting that the former are more in-depth and expensive, while the latter offer a diversity of opinions. Skills and procedures necessary for effective learning are presented. It is suggested to integrate both formats to enrich the educational experience.
Keywords: textbooks; newspapers; education; diversity